Nine years' experience of physiological correction of tricuspid atresia: long-term results and current surgical approach. Issue 10 (October 1982) - Ottenkamp, J; Rohmer, J; Quaegebeur, J M; Brom, A G; Fontan, F
Abstract : Fontan's correction has been performed without early death in 24 consecutive patients with tricuspid atresia. Eighteen patients had ventriculoarterial concordance (group I) and six discordance (group II). Late death related to infections occurred in three patients. The follow-up time in group I (16 survivors) ranges from 1 year 10 months to 7 years 5 months (mean 3 years 8 months) and in group II (five survivors) from 2 years 1 month to 5 years 6 months (mean 3 years 6 months). Early postoperative cardiac catheterisation showed arterial pulsatile pressure recordings in the pulmonary artery only in two patients in group I, in whom a valved conduit was used to connect the right atrial appendage with the outlet chamber. Patients with a valved conduit connected with either the pulmonary artery (group II) or the outlet chamber (two patients of group I) showed better preservation of right atrial contractions angiocardiographically and scored better in exercise tests than did patients with a non-valved conduit (14 patients of group I). In the latter patients evidence of regurgitant bloodflow from the outlet chamber into the right atrium was found. Reoperation was necessary in two patients. The outlet chambers showed a substantial increase in diameter after operation. No disturbances of kidney or liver function were found up to seven years after operation. The clinical condition has improved considerably in all survivors. It is concluded that the use of a valved conduit is preferable for connecting the pulmonary artery directly in cases of tricuspid atresia with ventriculoarterial discordance or the outlet chamber when there is ventriculoarterial concordance.